(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
The geological mapping and the biostratigraphic study of Neogene sediments outcropping near Palmariggi, a small area between Otranto and Maglie (Puglia), have been carried out. Above the dolomitic limestone units of the Cretaceous-Oligocene platform three sedimentary cycles have been recognized, one of Miocene and two of Pliocene age. The first cycle consists of two units: the Pietra leccese and the overlying Calcareniti di Andrano; the second cycle is represented by the Lèuca Formation and the last cycle by the Uggiano la Chiesa Formation. The pre-Neogene units are affected by a folding episode with major structures trending NNW- SSE. A subsequent tectonic event characterized by folds with axial directions interferring with the previous one has been detected in the pre-Neogene units. The latter deformation affects also the Miocene successions. Both the previous deformative episodes control the outcrop distribution of the Neogene sediments, preserved in the low structural sites such as synclinal cores. In the Palmariggi area an extensional tectonics of pre-Pliocene age follows the folding related to the compressive episodes. The normal faults linked to this late extension, show a NNW-SSE trend.